MECHANICAL SET MODELING OF AGRICULTURAL IMPLEMENT FOR SWEET POTATO PLANTING - Khatib, S. K. [UNESP]; Fregoneze, T. O. [UNESP]; Fávaro, V. F.S. [UNESP]; Santos, P. S.B. [UNESP] (Universidade Estadual Paulista - Campus de Tupa, 2020)
The present work brought together concepts of technical design (types of lines, dimensions, perspectives, orthographic projections in the 1st dihedral and cuts) to model a mechanical subset of an agricultural implement used for planting sweet potatoes, where it was necessary to seek real measures of the equipment for the realization of the 3D model and also of the orthographic projections through the Autodesk Fusion 360 software, which has a free license. It was possible to perceive the importance of these concepts in a real application, which to observe through technical drawing, that all engineering projects start through the visualization of ideas, saving time and money from agricultural machinery manufacturers.
MODELAGEM DE CONJUNTO MECÂNICO DE IMPLEMENTO AGRÍCOLA PARA PLANTIO DE BATATA DOCE
Keywords: Agricultural machine; Modeling; Sweet potato; Technical drawing